Development and evaluation of a species-specific PCR assay for the detection of Brucella ovis infection in rams - Xavier, Mariana N.; Silva, Teane M.A.; Costa, Erica A.; Paixao, Tatiane A.; Moustacas, Valeria S.; Carvalho Junior, Custodio A.; Sant’Anna, Felipe M.; Robles, Carlos Alejandro; Gouveia, Aurora M.G.; Lage, Andrey P.; Tsolis, Renee M.; Santos, Renato L. (Elsevier, 2021)
Brucella ovis infection is a major cause of epididymitis and infertility in rams, resulting in reproductive failure and significant economic losses worldwide. The goal of this study was to develop a PCR test targeting specific B. ovis genomic sequences. Specific primer pairs were designed targeting 12 of those ORFs. Samples of blood, serum, semen, urine, and preputial wash were collected from experimentally infected rams (n = 9) every other week up to 180 days post infection (dpi), when tissue samples were obtained. Blood, serum, semen, urine, and preputial wash samples were obtained, in weekly intervals for 1 month, from eight rams belonging to a B. ovis-free flock. Semen samples were also obtained from rams belonging to naturally infected flocks (n = 40). The limit of detection of this PCR protocol was 100, 10, and 1 CFU/mL for semen, urine and prepucial wash samples, respectively. Sensitivity and specificity values obtained with this PCR method were similar to that of bacteriology when evaluating biological samples. Agreement between PCR and bacteriology results was greater than 90%. These results clearly indicate that this speciesspecific PCR method is highly efficient for the diagnosis of B. ovis infection in semen, urine, preputial wash and tissue samples from infected rams.